2022
DOI: 10.1186/s13578-022-00771-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA in extracellular vesicles: from evolution to its current application in health and disease

Abstract: Extracellular vesicle (EV) secretion is a highly conserved evolutionary trait in all organisms in the three domains of life. The packaging and release of EVs appears to be a bulk-flow process which takes place mainly under extreme conditions. EVs participate in horizontal gene transfer, which supports the survival of prokaryotic and eukaryotic microbes. In higher eukaryotes, almost all cells secrete a heterogeneous population of EVs loaded with various biomolecules. EV secretion is typically higher in cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 105 publications
(98 reference statements)
0
65
0
Order By: Relevance
“…Even in case of DNA associated to the surface of (O)MVs, it was demonstrated that this DNA is involved in HGT: for instance, it was reported that DNase treatment of OMVs from Porphyromonas gingivalis impairs the efficiency of gene transfer 8 , 43 . Localization of DNA associated to MVs probably depends on their biogenesis, regarding either viable cells or dying ones: for example, in the latter case, DNA could also be associated to MVs by sticking on the surface of released vesicles 44 . This kind of cargo loading might be likely in Streptomyces , as programmed cell death is known and exerts a relevant role in the morpho-physiological differentiation of these bacteria 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Even in case of DNA associated to the surface of (O)MVs, it was demonstrated that this DNA is involved in HGT: for instance, it was reported that DNase treatment of OMVs from Porphyromonas gingivalis impairs the efficiency of gene transfer 8 , 43 . Localization of DNA associated to MVs probably depends on their biogenesis, regarding either viable cells or dying ones: for example, in the latter case, DNA could also be associated to MVs by sticking on the surface of released vesicles 44 . This kind of cargo loading might be likely in Streptomyces , as programmed cell death is known and exerts a relevant role in the morpho-physiological differentiation of these bacteria 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes also contain multiple kinds of DNAs, including single-stranded, double-stranded, genomic, and mitochondrial DNAs. Certain inflammatory processes and cell aging are thought to rationalize the presence of DNA in exosomes . There is more DNA in exosomes derived from cancer cells than from healthy cells.…”
Section: Characterization Of Exosomesmentioning
confidence: 99%
“…This is both a challenge and an opportunity for future research. The technical methods to distinguish DNA packaged during EV generation and passively released DNA (NETs, apoptotic bodies) are not yet sufficiently established [ 217 ]. The challenge is compounded by the large stimulus- and biological context-dependent variability of NETs and EVs.…”
Section: Discussionmentioning
confidence: 99%